2011
DOI: 10.1007/s12205-011-1360-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of flow patterns and energy dissipation over stepped chutes on aeration efficiency

Abstract: Stepped chutes that are commonly used for gabion weirs, river training, irrigation channels, and storm waterways have become popular in recent years mainly due to the intrinsic low-cost and the speed of construction. Stepped chutes are used also for in-stream re-aeration and in water treatment plants to enhance the air-water transfer of atmospheric gases and of volatile organic components. In a stepped chute, the provision of steps can produce significant energy dissipation. This paper seeks the effect of ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Also a change in the number of steps does not change the flow depth on the spillway crest for similar discharges. According to the equations 10 and 11 and also Baylar et al [28] classification, it could be stated that the flow surface has a series of fluctuations in all three discharges in the stepped spillway with 6 steps, in other words the transition flow regime is present in this state. The transition flow regime is only created in the discharge 0.075 m 3 /s when 8 steps are used.…”
Section: Turbulent Kinetic Energymentioning
confidence: 99%
See 1 more Smart Citation
“…Also a change in the number of steps does not change the flow depth on the spillway crest for similar discharges. According to the equations 10 and 11 and also Baylar et al [28] classification, it could be stated that the flow surface has a series of fluctuations in all three discharges in the stepped spillway with 6 steps, in other words the transition flow regime is present in this state. The transition flow regime is only created in the discharge 0.075 m 3 /s when 8 steps are used.…”
Section: Turbulent Kinetic Energymentioning
confidence: 99%
“…They also came to the conclusion that the k-εturbulencemodelhadthemostcapabilityinsimulatingtheflowoversteppedspillwaysincomparisonwiththe other turbulence models. Baylar et al [28] examined energy dissipation and flow pattern on the stepped chutes. They concluded that flow aeration efficiency increased as the energy dissipation increased.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from experimental studies, thanks to the advances in the computational performance of computers, numerical methods have also been successfully used to study the detailed flow properties in complex contexts [12][13][14][15]. Baylar et al [16] numerically examined the energy loss and aeration efficiency of the stepped chutes and found that both of them in nappe flow regime were greater than that of the skimming flow regime. Numerical simulations by researchers [17][18][19] demonstrated its high performance in investigating the detailed flow field and pressure distribution over stepped spillway.…”
Section: Introductionmentioning
confidence: 99%
“…The hydraulic design of stepped cascades, and in particular, characteristics of nappe flow, transition flow and skimming flow over stepped cascades has been studied experimentally by a number of investigators. Recently, Baylar ***Associate Professor, Civil Engineering Deptartment, Firat University, Elazig 23119, Turkey (Corresponding Author, E-mail: abaylar@firat.edu.tr) ***Assistant Professor, Civil Engineering Deptartment, Kahramanmaras Sutcu Imam University, Kahramanmaras 46100, Turkey (E-mail: munsal@ksu.edu.tr) ***Assistant Professor, Construction Education Deptartment, Firat University, Elazig 23119, Turkey (E-mail: fozkan@firat.edu.tr) and Emiroglu ( , 2004Emiroglu ( , 2005, Emiroglu and Baylar (2003) and Baylar et al (2006Baylar et al ( , 2007aBaylar et al ( , 2007bBaylar et al ( , 2011 did some detailed studies on the oxygen transfer efficiency of stepped cascades. Today, the applications of soft computing systems, such as neural networks, fuzzy logic, genetic algorithms, least squares support vector machines, and etc.…”
Section: Introductionmentioning
confidence: 99%